JEMAAH MAHASISWA SALAFI DI MASJID POGUNG YOGYAKARTA - Arbi Mulya Sirait (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
This paper aims to describe the religious attitudes of salafi students who emerge and develop through religious and social activities in the Pogung Dalangan Mosque and the Pogung Raya Mosque, and so the extent of the functions and roles of the mosque in facilitating religious activities. In the final section, their social life and their responses to several developing issues are presented. To get the data in this paper, the writer uses interview, questionnaire and observation methods. The total sample in this study amounted to twenty-seven salafi students. This research uses the theory of religiosity and the sociology of religion theory. Based on the results of research conducted it can be concluded that in terms of beliefs, the principles used by this community are basically the same as Muslims in general, only in terms of expression, they are more strict and consistent as far as they understand. In the aspect of worship, this community only truly carries out religious activities that are based on religious norms, without opening up opportunities for cultural integration. They always try to maintain their religious originality to avoid things that threaten religion. Salafi students also do not provide positive response to western thought such as democracy, pluralism and gender equality. They assume that these thoughts cannot be compared with the teachings of Islam.